Senegal : First Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria-Press Release; and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses Senegal's First Review Under the Policy Support Instrument (PSI) and Request for Modification of Assessment Criteria. Program performance through September was broadly satisfactory. All end-June assessment criteria were met but the end-June indicative target on tax revenue was missed because of a shortfall in customs revenue. Continued rationalization and better control of public expenditure helped meet the fiscal deficit target despite the shortfall in revenue. All structural benchmarks were met. In line with the IMF's new debt limits policy, the authorities request the removal of the nonconcessional external debt assessment criteria. The IMF staff supports the authorities' request for the completion of the first PSI review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet